Practices of Writing in Ethnographic Work. (February 2021) - Schindler, Larissa; Schäfer, Hilmar
Although the practice of writing is key to the production of ethnographic knowledge, the topic remains understudied. Using material from our own ethnographic research in the fields of air travel and cultural heritage as data, we develop a reflexive account of ethnographic writing. We examine in detail the practices of jotting down observations, writing field notes, analytic annotating, ordering and rearranging, and drafting and revising papers. The article takes a praxeological stance, conceptualizing writing as a practice that is simultaneously cognitive, embodied, and material. Our analysis finds that writing influences and shapes all stages of ethnographic work, from orienting perception by setting an appropriate mode of attention to organizing the work itself, e.g., by keeping to-do lists. Writing does not simply communicate ethnographic insights, but—as a result of the activity of texts—it also generates them.